On safety and security requirements in emerging ubiquitous computing models - Osborn, E; Simpson, A (Oxford University Press, 2015)
The fields of safety and security are converging due to a number of factors, including the rise in system interconnectivity and an increased dependence on the Internet as part of critical national infrastructures. Partly as a reflection of this, there is a wealth of literature pertaining to the increasing interdependence between safety and security. While much of this research has been concerned with large-scale industrial systems, the rapid emergence of what might be termed Consumer Cyber Physical Systems (Consumer CPS) means that it is crucial that such issues are considered in that context also. We evaluate the motivations for implementing Consumer CPS and the novelty of safety and security concerns that such systems give rise to. This evaluation is subsequently used to establish a collection of cyber security requirements for this emerging domain. We also consider how these requirements might impact upon product lifecycles. Our contribution is motivated and illustrated by three representative scenarios.